Cybersecurity of remote work migration: A study on the VPN security landscape post Covid-19 outbreak - Kushtrim Qollakaj; Lukas Einler Larsson; Suejb Memeti (Array)
The Covid-19 pandemic led to an unprecedented reliance on Virtual Private Networks (VPNs) for remote work, exposing critical vulnerabilities in global cybersecurity infrastructures. As organizations rapidly transitioned to remote operations, many lacked the necessary security measures to protect their VPN systems, making them prime targets for cybercriminals. This study synthesizes findings from 106 studies (2020–2023) to analyze the evolution of VPN-targeted cyberattacks, the tactics employed by threat actors, and effective mitigation strategies.Our analysis reveals that the widespread adoption of remote work triggered a 238% surge in VPN-targeted attacks between 2020 and 2022, as adversaries exploited vulnerabilities, misconfigurations, and inadequate security policies. Both independent cybercriminals and state-sponsored actors leveraged phishing, ransomware, and advanced persistent threats (APTs) to gain unauthorized access to corporate networks. In many cases, organizations struggled with outdated VPN protocols, weak authentication mechanisms, and insufficient network segmentation, allowing attackers to infiltrate systems with minimal resistance.To address these challenges, we propose a VPN Hardening Framework incorporating strong authentication, robust encryption, secure configurations, and continuous monitoring, expected to significantly reduce breach risks and enhance VPN resilience in the post-pandemic era. Additionally, we highlight emerging cybersecurity trends, including the role of zero-trust architectures, quantum-resistant encryption, and AI-driven intrusion detection in fortifying VPN security against evolving threats.